Radiation protection and safety measurements in nuclear medicine departments: students perspective - Sayed, Inayatullah Shah; Mahmood, Muthahharah Nabilah Syuhada (Research Publish Journals, 2016)
Due to the introduction of new ionizing radiation related diagnostic and therapeutic practices, usage of ionizing radiation in medicine is growing. Radiation protection education is important in developing safety culture among the radiation workers. Also, it is vital to make sure the workers are well educated, trained and knowledgeable. Beside the well recognized working procedures, availability & utilization of relevant protective equipment, and an effective monitoring program are indispensable factors in making sure that radiation workers in nuclear medicine department are satisfactorily protected. Hence, the purpose of this work was to study the availability of necessary tools and compliance of radiation protection and safety rules by the staff working in nuclear medicine departments in Malaysia through student’s observation. A questionnaire was distributed to 65 students those spent more than two months of clinical practice at the nuclear medicine department. It is concluded from the results that the overall proper implementation of radiation protection and safety was followed by the staff of nuclear medicine departments. With the improvement in radiation protection program, it is expected that more workers can comply the radiation protection and safety rules.